Thrombosis in Pregnant Women with Hemolytic Anemia - Papadakis, Emmanouil; Brenner, Benjamin (Seminars in Thrombosis and Hemostasis, 2022)
Hemolytic anemias are a group of uncommon disorders affecting both genders, frequently occurring at the reproductive age. While a link between hemolysis and hypercoagulability has been suggested based on the elucidation of certain involved pathophysiological mechanisms, the extent of thrombotic risk in pregnant women with hemolytic anemia remains debatable. Due to the paucity of pregnancy-related data, risk assessment of gestations in women with hemolytic anemia is complicated. This review will highlight the latest advances in the diagnosis and management of these challenging disorders in pregnancy.
Keywords: hemolytic anemias; pregnancy; venous thromboembolism